Autophagic flux-lipid droplet biogenesis cascade sustains mitochondrial fitness in colorectal cancer cells adapted to acidosis - Xiaojie Liu; Xue Sun; Wenqing Mu; Yanan Li; Wenqing Bu; Tingting Yang; Jia Zhang; Rui Liu; Jiayu Ren; Jin Zhou; Peishan Li; Yufang Shi; et al. (Cell Death Discovery)
Abstract Cancer development is associated with adaptation to various stressful conditions, such as extracellular acidosis. The adverse tumor microenvironment also selects for increased malignancy. Mitochondria are integral in stress sensing to allow for tumor cells to adapt to stressful conditions. Here, we show that colorectal cancer cells adapted to acidic microenvironment (CRC-AA) are more reliant on oxidative phosphorylation than their parental cells, and the acetyl-CoA in CRC-AA cells are generated from fatty acids and glutamine, but not from glucose. Consistently, CRC-AA cells exhibit increased mitochondrial mass and fitness that depends on an upregulated autophagic flux-lipid droplet axis. Lipid droplets (LDs) function as a buffering system to store the fatty acids derived from autophagy and to protect mitochondria from lipotoxicity in CRC-AA cells. Blockade of LD biogenesis causes mitochondrial dysfunction that can be rescued by inhibiting carnitine palmitoyltransferase 1 α (CPT1α). High level of mitochondrial superoxide is essential for the AMPK activation, resistance to apoptosis, high autophagic flux and mitochondrial function in CRC-AA cells. Thus, our results demonstrate that the cascade of autophagic flux and LD formation plays an essential role in sustaining mitochondrial fitness to promote cancer cell survival under chronic acidosis. Our findings provide insight into the pro-survival metabolic plasticity in cancer cells under microenvironmental or therapeutic stress and imply that this pro-survival cascade may potentially be targeted in cancer therapy.